1
AIEEE 2004
+4
-1
The equation of the straight line passing through the point $$(4, 3)$$ and making intercepts on the co-ordinate axes whose sum is $$-1$$ is :
A
$${x \over 2} - {y \over 3} = 1$$ and $${x \over -2} +{y \over 1} = 1$$
B
$${x \over 2} - {y \over 3} = -1$$ and $${x \over -2} +{y \over 1} = -1$$
C
$${x \over 2} + {y \over 3} = 1$$ and $${x \over 2} +{y \over 1} = 1$$
D
$${x \over 2} + {y \over 3} = -1$$ and $${x \over -2} +{y \over 1} = -1$$
2
AIEEE 2004
+4
-1
Let $$A\left( {2, - 3} \right)$$ and $$B\left( {-2, 1} \right)$$ be vertices of a triangle $$ABC$$. If the centroid of this triangle moves on the line $$2x + 3y = 1$$, then the locus of the vertex $$C$$ is the line :
A
$$3x - 2y = 3$$
B
$$2x - 3y = 7$$
C
$$3x + 2y = 5$$
D
$$2x + 3y = 9$$
3
AIEEE 2004
+4
-1
Out of Syllabus
If the sum of the slopes of the lines given by $${x^2} - 2cxy - 7{y^2} = 0$$ is four times their product $$c$$ has the value :
A
$$-2$$
B
$$-1$$
C
$$2$$
D
$$1$$
4
AIEEE 2004
+4
-1
Out of Syllabus
If one of the lines given by $$6{x^2} - xy + 4c{y^2} = 0$$ is $$3x + 4y = 0,$$ then $$c$$ equals :
A
$$-3$$
B
$$-1$$
C
$$3$$
D
$$1$$
JEE Main Subjects
Physics
Mechanics
Electricity
Optics
Modern Physics
Chemistry
Physical Chemistry
Inorganic Chemistry
Organic Chemistry
Mathematics
Algebra
Trigonometry
Coordinate Geometry
Calculus
EXAM MAP
Joint Entrance Examination